Synchronised output regulation of leader-following heterogeneous networked systems via error feedback. Issue 4 (11th March 2016) - Li, Yanjun; Wang, Xuejie; Xiang, Ji; Wei, Wei
Abstract : A dynamic error feedback controller is presented for the synchronised output regulation (SOR) of leader-following heterogeneous linear networked systems. The nodes in the networked systems are divided into two kinds: the leader node accessible to the regulated error and the following nodes inaccessible to the regulated error but accessible to the relative output errors with respect to their neighbouring nodes. By using the small-gain theorem, a sufficient criterion for the SOR problem is developed for more general networks. This criterion can be regarded as imposing an additional H ∞ constraint on the classical output regulation problem. The synthesis problem is then addressed by means of linear matrix inequality technique. The efficacy of the analytic results is illustrated by simulation examples.